Premature Ovarian Failure - Bulletti, Francesco Maria; Coccia, Maria Elisabetta; Guido, Maurizio; Palagiano, Antonio; Sciorio, Romualdo; Giacomucci, Evaldo; Giacomucci, Evaldo; Bulletti, Carlo (Clinical Journal of Obstetrics and Gynecology, 2025)
Objective: To provide a rigorous, multidisciplinary synthesis of the epidemiological, genetic, immunological, and environmental factors contributing to Premature Ovarian Failure (POF), with particular attention to regional disparities, occupational exposures, the impact of chemotherapy, the occurrence and recurrence of endometrosis, and emerging fertility preservation strategies. Design: A structured literature review with an emphasis on recent advances in genetic and immunological understanding. Setting: Academic research and clinical insights from multidisciplinary contributors. Patients: Individuals diagnosed with POF as reported in the literature. Interventions: Review of literature concerning epidemiology, genetic mutations, immunological disorders, and surgical outcomes linked to POF. Main outcome measures: Identification of both established and emerging risk factors, validation of genetic and immunological markers, and clarification of diagnostic and preventive clinical approaches. Results: The prevalence of POF varies globally, affecting 1% of women under 40. Genetic factors, particularly mutations in the FMR1 and BMP15 genes, play a significant role, alongside autoimmune diseases. Chemotherapy is a leading iatrogenic cause, while endometriosis and ovarian cyst surgeries significantly contribute to diminished ovarian reserve. Conclusion: POF is a multifactorial condition with rising incidence in specific subgroups. Improved early detection, standardized biomarker use, and expanded access to fertility preservation are essential. Targeted genomic and occupational risk screening may enable personalized interventions. Further genomic studies are needed to elucidate rare mutations and their impact.